Perbandingan Teknik Ovariektomi dan Ovariohisterektomi pada Anjing Lokal Indonesia - Siswandi, Riki; Soehartono, R. Harry; Kale, Nadya Daramuli (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2025)
Gonadectomy is a common procedure to control dog populations and prevent reproductive diseases. Ovariectomy (OVE) and ovariohysterectomy (OH) are the primary techniques, although their relative efficiency remains under debate. This study compared both methods based on hematological parameters, surgical duration, blood loss, wound healing, progesterone levels, body weight, and postoperative behavior in female dogs. This experiment were using 14 female domestic dogs were divided into OVE and OH groups. Surgeries were performed under general anesthesia, and outcomes were analyzed statistically. Postoperatively, hematocrit and erythrocyte counts significantly decreased in OH group (p<0.05), while white blood cell counts were higher than in OVE (p<0.05), indicating stronger inflammatory response. OVE had a shorter surgical time (56.18 ± 7.10 min vs. 84.41 ± 24.28 min), lower blood loss (4.91 ± 2.60 g vs. 46.02 ± 39.06 g), and faster wound healing (4.57 ± 0.76 days vs. 5.91 ± 1.24 days) (p<0.05). There was no significant differencs in progesterone level one month post surgery between the OVE and OH groups (0.67 ± 0.30 ng/mL and 0.48 ± 0.29 ng/mL, respectively). Likewise, no significant difference were observed in body weight gain, as well as in grooming, sleeping, drinking, exploration and play behaviours between the groups after nine weeks of observation. In conclusion, both techniques effectively reduce plasma progesterone concentration and support body weight gain, but OVE offers greater surgical efficiency, faster recovery, and fewer hematological alterations, highlighting its potential as the optimal technique for sterilizing.